“Enemies of the People” in the Democratic People’s Republic of Korea: The Political Meaning of Human Rights Violations Against Them - Yi, Eunwon (Power Shifts in East Asia and Their Implications for Asia–Europe Relations, 2019)
Over the last several decades, the Democratic People’s Republic of Korea (DPRK)’s government has repeatedly produced a number of “enemies of the people.” This article contends that the “enemies” in the DPRK have been produced by political decisions in the name of popular sovereignty, based on post-colonialism and socialism. The principal goal of this article is to identify the political meaning of violations against the “enemies of the people” and to shed light on the problems of “politicized human rights.”